Probiotics : advanced food and health applications - Brandelli, Adriano (Elsevier Academic Press, 2021)
Probiotics: Advanced Food and Health Applications presents the functional properties and advanced technological aspects of probiotics for food formulation, nutrition, and health implications. Specifically, the book addresses the fundamentals of probiotics, from their discovery to actual developments, the microbiological aspects of the main genus showing probiotic properties, the natural occurrence of probiotic strains in foods, the development of nutraceuticals based on probiotics, and the relationship of probiotics to health. The book also includes a discussion on regulatory aspects. This book is an excellent resource for food scientists, nutritionists, dieticians, pharmaceutical scientists, and others working with probiotics or studying related fields.